KEMAMPUAN MEMPARAFRASAKAN PUISI KERENDAHAN HATI KARYA TAUFIK ISMAIL KE EKSPOSISI SISWA KELAS X MAN 039 TEMBILAHAN - Indah Fitriani; Nursal Hakim; Abdul Razak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study investigated the ability of paraphrase a poem by Taufik Ismail humility to exposition class X MAN 039 Tembilahan. The aim of this study was to obtain data on the ability of paraphrase a poem by Taufik Ismail humility to exposition class X MAN 039 Tembilahan. The ability of paraphrase of the aspects of understanding the content and paraphrased. This study is a quantitative-descriptive. This research data is data test capabilities humility paraphrase a poem by Taufik Ismail to exposition class X MAN 039 Tembilahan. Instruments in this research is a form of poetry texts given to members of the sample. The data collection was done by using the test. The population in this study were 301 students with a total sample of 168 students. Data were analyzed with descriptive methods. The validity of the data obtained through data validation. Research results seen from the test results the ability of paraphrase a poem by Taufik Ismail humility to exposition class X MAN 039 Tembilahan. Seen from the aspect of understanding the content obtained average value amounted to 70.07 with a low category. Then, from the aspect paraphrase obtained average value amounted to 73.96 with the medium category.Keywords: paraphrasing, understand the content of the poem, poetry, exposition.